Metropolitan migration and spatial housing markets: A geographical study in Melbourne. (April 2021) - Li, Tiebei; Shiran, Solmaz Jahed; Dodson, Jago
Abstract: Metropolitan internal migration is an important process driving urban structure and settlement patterns. This research explores the geographical movement of metropolitan migration in Melbourne at a disaggregate spatial scale. Several spatially based techniques are employed, from which the complex patterns of migration are identified. The implications of migration movements for urban structure and infrastructure are also examined. This paper then links the migration flows to a spatial housing market analysis, and finds that urban variations in housing utility and housing prices are important factors influencing patterns of migration. In addition, new dwelling development programs generate new vacancy chains which shape residential migration toward outer urban areas. Drawing conclusions from this analysis, our research recommends more effective government approaches to fostering investment in housing-related infrastructure in Australian cities, and it discusses how broader policy and investment can align to drive settlement patterns which optimise productivity and liveability and minimise negative effects. Highlights: Residents in the established urban zones exhibit strong outward migration. Moves from urban fringe areas are inward. Residents tend to migrate within a local region to retain the connection with existing social networks or job markets. Urban internal migration is influenced by housing market, of which housing utility and affordability are important factor. New housing policy is needed to improve the housing consumption and consequently the patterns of urban internal migration.